Optimalisasi Pembelajaran Tajwid dan Pembinaan Karakter Santri melalui Metode Hafalan - Moh. Syairozi (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2025)
This study aims to determine the effectiveness of the Hidayatus Shibyan book memorisation method in improving understanding of tajwid and shaping the character of students at Madrasah Diniyah Al-Falah. A qualitative approach was used with direct observation and in-depth interviews with teachers and students. The results of the study show that the memorisation method, which is carried out actively, interactively, and supported by the high enthusiasm of the teachers, is able to improve the memorisation ability of students, strengthen their understanding of tajwid rules, and instil Islamic character values. In addition, the use of verses in the Hidayatus Shibyan facilitates students' memorisation and comprehension, making learning more enjoyable and effective. Teachers' freedom in choosing teaching methods and support from madrasah administrators also play a role in the success of the learning process. Thus, this memorisation method is highly relevant and effective as a learning strategy for tajwid and Islamic character education at the elementary level. This research is expected to contribute to improving the effectiveness of tajwid learning, strengthening Islamic character education, developing learning strategies, and providing inspiration in the development of Islamic education curricula.